ANALYSIS OF MARKETING STRATEGY AND SUPPORTING FACTORS FOR INCREASING ONLINE SALES (ON MARKETPLACE: SHOPEE) MEN'S & WOMEN'S CLOTHING PRODUCTS BRAND SEYES - Hamsinah Hamsinah (International Journal of Education, Information Technology, and Others, 2018)
The purpose of this research is to use the marketplace as a product sales medium for entrepreneurs of Seyes brand t-shirts for men and women in the Shopee Marketplace, how to find obstacles and strategies to increase product sales in each marketplace according to the promo style (features) owned by the marketplace. Shopee, looking for factors from t-shirt products or fashion trends that can be used as a support for increasing sales in E-business (Shopee Marketplace), to find weaknesses and advantages of selling in the marketplace that can be used as material for evaluating global company sales (offline or online). In the research method, it has been explained that the researcher uses a qualitative approach. General strategy and explanation of strategic direction: Total score of strengths: 3.90, Total score of weakness: - 2, Total score of opportunity: 3.25, Total score of threats: - 1.20. Based on this score, the determination of the company's position can be drawn as a Swot Brand Seyes matrix described in the quadrant graph, Quadrant I with an area of 12.7 Matrix Rank I shows the priority of the Growth strategy, Quadrant III with an area of 2.4 Matrix Rank 2 shows the priority Combination , Quadrant II with an area of the Matrix – 6.5 Rank 3 shows the priority of the Stability strategy, Quadrant IV with an area of the Matrix -4.68 Rank 4 shows the priority of the Downsizing Strategy. The results show that Brand Seyes' position is in quadrant I (Strong Competition) and to support this, the following general strategies can be used: expanding the sales network, strengthening promotions and advertising by maximizing the features provided by the shopee marketplace which has a wide reach, especially on social media and advertising. in other digital media, more innovative in the development of product style and design, improve services and strengthen brand image so that consumers feel comfortable and will be sure to be loyal.